Peningkatan Keterampilan Penggunaan Fitur Mail-Merge Microsoft Word Bagi Guru dan Staf SMK Muhammadiyah Seputih Raman - Dewi Asiah Shofiana; Yohana Tri Utami; Yunda Heningtyas; Rizky Prabowo (Universitas Teknokrat Indonesia, 2023)
Development of information technology plays an important role not only in the industrial economic section, but also in education. Information technology is applied at almost every level of education to support the performance of teachers and academic staff. One software commonly used for education and administration is Microsoft Word. The Microsoft Word software has many features, however most of the features are still unfamiliar to some users, including teachers and staff at SMK Muhammadiyah Seputih Raman, Central Lampung. Many teachers and staff are still unfamiliar with the tools available in Microsoft Word, including the mail-merge function. Therefore, our team provided training for 24 participants of teachers and staffs to improve their understanding of Microsoft Word features through lectures, discussions, and hands-on practice. Evaluation results show that after the training, 79% of the participants understand the material provided and almost all participants showed an improvement in the test.